Kebijakan Hukum Pidana terhadap Penyalahgunaan Narkotika Pasal 127 Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika - Utami, Jofinka (Wajah Hukum, 2025)
Legal policy against drug abusers and addicts to undergo medical and social rehabilitation is regulated in Article 127 of Law Number 35 of 2009 concerning Narcotics. However, there are differences of opinion between this Article and related Articles which cause the implementation in the field to be less than appropriate. This study aims to determine the legal policy on Article 127 of Law Number 35 of 2009 concerning Narcotics. The research method used is normative with a statutory regulatory approach and a case approach. The scope or object of this study is the criminal law policy on Article 127 of Law Number 35 of 2009 concerning Narcotics. The main legal sources used include primary legal materials such as Law Number 35 of 2009 concerning Narcotics, secondary legal materials consisting of books and journals by legal experts, and tertiary legal materials used include related dictionaries and encyclopedias. The results of the study show that there are several decisions that were charged with Law 127 of Law Number 35 of 2009 concerning Narcotics who were not given the opportunity for rehabilitation, which is not in accordance with the contents of Article 127 of Law Number 35 of 2009 concerning Narcotics.